Science Mapping of Open-Access Articles on Data Visualisation: A Scopus-based Analysis (LIS TODAY, 2024)
The prime objective of the present study is to analyze the impact of open-access  publishing on research publications in data visualization journal research papers  using scientometric indicators and science mapping techniques. A total of 9,018  publication records were extracted from the Scopus database for five years,  from 2018 to 2022. The parameters used for the present study are open-access  publication trends and their impact on the number of publications and citations,  most prolific authors, organizations, countries, journals, etc. The study results  indicate that 60.55% of articles on data visualization were published as open  access, and the trend of open-access publication has grown exponentially. The  study further found that open-access articles have a better academic impact than  overall articles published. Huamin Qu of Hong Kong University of Science and  Technology has contributed the highest number (22) of open-access articles on  data visualization; the authors affiliated with the Centre National de la Recherche  Scientifique (CNRS), Paris, have contributed the highest (116) OA articles; and  the United States was the topmost productive country with the highest (1,809) OA  articles. IEEE Transactions on Visualization and Computer Graphics was the most  preferred journal among researchers on data visualization to publish their research  as open-access articles.
Keywords: Data Visualization; Open Access; Science Mapping; Scopus Database; Publishing Trends